Effect of the Quality of Tourism Objects and Brand Image of Tourism Aspects on the Tourism City’s Image the Case of Tawangmangu, Indonesia - Prianti, Diani Mustika (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study examines the effects of the quality of the tourism model and the aspects of the brand image of tourism on the image of Tawangmangu as a tourism city. The study was conducted in the Tawangmangu Sub-District of the Karanganyar Regency in Central Java, Indonesia, at the beginning of 2024. Purposive sampling was used to select a sample of 100 domestic travelers, all of whom responded to a standardized questionnaire. Software called SMARTPLS was used to analyze the data. The results showed that the quality of the tourism model and the brand image of its tourism components had a favorable and considerable impact on Tawangmangu's reputation as a tourist destination, both individually and collectively. Furthermore, the study discovered that the quality of the tourist model positively and significantly impacted the brand image of tourism-related features. Based on the findings, Tawangmangu should develop a strong tourism image by first creating a quality tourism model, which includes herbal tourism attractions, natural and cultural tourism objects, supporting facilities, and tourism services. A compelling brand image should be developed, encompassing destination naming, city environment, tourism logos, and identity. Additionally, the study shows that Tawangmangu's tourist model quality is a significant factor in determining how the tourism industry is portrayed.